A cross-sectional and longitudinal evaluation of serum creatinine as a biomarker in spinal muscular atrophy - Xin Zhao; Zhenxiang Gong; Han Luo; Zehui Li; Rong Gao; Kangqin Yang; Wenhua Deng; Sirui Peng; Li Ba; Yang Liu; Min Zhang (Orphanet Journal of Rare Diseases, 2024)
Abstract Objective Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disease characterized by proximal muscle weakness and atrophy. The increasing availability of disease-modifying therapies has prompted the development of biomarkers to facilitate clinical assessments. We explored the association between disease severity and serum creatinine (Crn) levels in SMA patients undergoing up to two years of treatment with nusinersen. Methods We measured serum Crn levels and assessed function performance using the Hammersmith Functional Motor Scale-Expanded (HFMSE), Medical Research Council Scale (MRC), 6-Minute Walk Test (6MWT), ulnar Compound Muscle Action Potential (CMAP), and forced vital capacity (FVC) in a cohort comprising 28 adolescent and adult patients with SMA. The association between Crn and disease severity was investigated through partial rank correlation analysis and linear mixed models while accounting for age, gender, and BMI. Linear models were employed to predict functional performance. Results 28 SMA patients and 28 gender- and age-matched healthy controls (HCs) were included, resulting in a dataset of 185 visits. Compared to HCs, SMA patients exhibited significantly lower Crn values ​​(67.4 ± 14 vs. 23.7 ± 14.8 umol/L, p<0.0001). After adjusting for age, sex, and BMI, Crn showed positive correlations with the HFMSE (p<0.0001, r = 0.884), MRC (p<0.0001, r = 0.827), FVC (p = 0.002, r = 0.730), and ulnar CMAP (p<0.0001, r = 0.807). Patients with SMN2 copy number ≥ 4 had nearly twice as high Crn levels as those with SMN2 copy number < 4 (34.1 ± 3.75 vs. 17.2 ± 2.52 umol/L, p = 0.00145). Ambulant SMA patients had more than double the Crn levels compared to non-ambulant ones (32 ± 2.33 vs. 12.9 ± 2.38 umol/L, p<0.0001). Furthermore, Crn explained that up to 83.5% of the variance in functional performance measured by HFMSE, MRC, and 6MWT was significantly higher than that of traditional biomarkers. Conclusions These findings suggest that Crn may be a potential biomarker for assessing disease severity in adolescents and adults with SMA, demonstrating its promise in clinical applications.